3a + 2b is an expression in algebra. If you make 3a + 2b equal to something then you can find the values of "a" and "b"
Lets say you make 3a + 2b equal to 23
3a + 2b = 23
Now find "a" and "b" to make this equation true...
3(5) + 2(4) = 23
15 + 8 = 23
23 = 23 Correct
So in this case a=5 and b=4
8a+2b
It is an expression that can be simplified to: 3a-2b+c
It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus
Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).
1
10a+7b undefined variables cannot be determined
-2a plus 3b
6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b
3a - 2b
7a-2b
= a + b - 2
3a + 2b = c (find a in terms of b and c)3a +2b -2b = c - 2b3a = c - 2b3a/3 = (c - 2b)/3a = (c - 2b)/3In order to find the value of a, you can give any values to b, and c (except a zero value).